Settlement Requirement in General Assistance - Daniel R. Mandelker (Washington University Law Quarterly, 1955)
The basic structure of the settlement laws still continues to be important to general assistance administration, especially in view of the fact that aid is often denied to non-settled persons as a matter of practice. This article will examine the law of settlement, consider its implications for persons applying for help, and determine whether and to what extent it belongs in a general assistance program.
Keywords: Public welfare; Social welfare